The Effects of Self-Controlled Video Feedback on the Learning of the Basketball Set Shot - Aiken, Christopher A.; Fairbrother, Jeffrey T.; Post, Phillip G. (Frontiers in Psychology, 2012)
Allowing learners to control some aspect of instructional support (e.g., augmented feedback) appears to facilitate motor skill acquisition. No studies, however, have examined self-controlled (SC) video feedback without the provision of additional attentional cueing. The purpose of this study was to extend previous SC research using video feedback about movement form for the basketball set shot without explicitly directing attention to specific aspects of the movement. The SC group requested video feedback of their performance following any trial during the acquisition phase. The yoked group received feedback according to a schedule created by a SC counterpart. During acquisition participants were also allowed to view written instructional cues at any time. Results revealed that the SC group had significantly higher form scores during the transfer phase and utilized the instructional cues more frequently during acquisition. Post-training questionnaire responses indicated no preference for requesting or receiving feedback following good trials as reported by Chiviacowsky and Wulf (2002, 2005). The nature of the task was such that participants could have assigned both positive and negative evaluations to different aspects of the movement during the same trial. Thus, the lack of preferences along with the similarity in scores for feedback and no-feedback trials may simply have reflected this complexity. Importantly, however, the results indicated that SC video feedback conferred a learning benefit without the provision of explicit additional attentional cueing.